2019
DOI: 10.30537/sijmb.v5i2.115
|View full text |Cite
|
Sign up to set email alerts
|

Profitability Paradox: Evidence from Commercial Banks in Pakistan

Abstract: It is generally believed that information technology (IT) impacts the organizational profitability positively however empirical evidence has remained inconclusive. This was first highlighted by Solow (1987), labelled as Solow’s paradox, and later labelled as profitability paradox by Beccalli (2007). The persistence of inconclusive empirical literature provides the impetus of this research to investigate the impact of different components of IT on banks profitability in Pakistan from 2009-2016 for a sample of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…Interestingly, our findings diverge from prior studies conducted by (Ernawati & Budiharjo, 2020;Mulyani, 2014), both of which identified a positive and substantial link between return on assets and capital structure. However, our conclusions align with Shahid et al (2016), who documented a negligible and negative impact of ROA on capital structure.…”
Section: 2 Effect Of Return On Asset On Capital Structuresupporting
confidence: 90%
See 2 more Smart Citations
“…Interestingly, our findings diverge from prior studies conducted by (Ernawati & Budiharjo, 2020;Mulyani, 2014), both of which identified a positive and substantial link between return on assets and capital structure. However, our conclusions align with Shahid et al (2016), who documented a negligible and negative impact of ROA on capital structure.…”
Section: 2 Effect Of Return On Asset On Capital Structuresupporting
confidence: 90%
“…This holds significance as a company's capital structure encompasses longand short-term debt, making fluctuations in the solvency ratio consequential for the overall structure. This discovery resonates with Shahid et al (2016) findings, demonstrating a significant interplay between leverage and capital structure. The solvency ratio is vital for businesses in devising capital structure strategies to achieve optimal arrangements.…”
Section: 3 Effect Of Long-term Debt To Equity Ratio On Capital Structuresupporting
confidence: 72%
See 1 more Smart Citation
“…Convergence marketing is concerned with providing banking services to customers who are familiar with and involved in the digital world. Even so, information technology can be a paradox that makes investing in information technology detrimental to the company (Hamid et al, 2018). Convergence marketing needs to first turn the investment in information technology into a competitive advantage to lead to performance.…”
Section: Mediating Effect Of Competitive Advantagementioning
confidence: 99%
“…Research on 42 branchless banks in Kenya found that investment in information technology reduced bank financial performance significantly (Dzombo et al , 2017). Likewise, research in Pakistan reveals the existence of an information technology paradox, namely, when certain components of information technology harm banking performance (Hamid et al , 2018). In line with this, a study in Lebanon found that investment in internet banking had no significant effect on the bank performance (Mahboub, 2018).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%